حماية حقوق المرأة في منظور التشريع الإماراتي والاتفاقيات والمعاهدات الدولية - خليفه محمد عبيد راشد عبود
The study aimed to identify the rules for the protection of women's rights in the perspective of UAE legislation and international conventions and treaties, in terms of showing the compatibility of legislation in the United Arab Emirates with the provisions of international conventions on the protection of women's rights in all fields and revealing their effectiveness in providing legal protection for women's rights and their compatibility with what was stated in international conventions related to the protection of women's rights. Laws on the protection of women's rights, which are in line with international conventions, such as the Anti-Discrimination and Hate Law, the Penal Code, the Law on Combating Human Trafficking, the Federal Labor Law, and the Personal Status Law. As the problem of the study is that there are many rights that are classified as basic rights for women, which are the rights stipulated in international conventions and treaties related to human rights, but in some countries international conventions on the protection of women's rights are not implemented, as the issue of protecting human rights is not limited to international conventions, but there is an important aspect related to the protection of women's rights, and this aspect is the legal aspect in domestic national laws, where legislation is integrated The problem of the study has a special dimension to the extent to which international conventions on the protection of women's rights are integrated with domestic laws so that there is no conflict between them. The study also shows the importance of the study from a scientific point of view in that it shows the legal context pursued by the UAE legislator in protecting women's rights by explaining the most important Emirati legislation that provides for the protection of women's rights, such as their right to life, their right to work, the protection of personal life, their rights to hold public office, education, marriage, physical integrity, litigation and other basic rights of women. One of the most prominent results of the study is that the United Arab Emirates grants women all their rights without derogation, and it also guarantees the protection of women's rights in all fields of life, despite the absence of a special law for the protection of women in the country, but there are many practical practices and authorities concerned with the protection of women's rights, and the United Arab Emirates is greatly interested in empowering women in all political, economic and social fields. One of the most prominent recommendations of the study is the need for the UAE legislator to enact criminal legislation for the protection of women's rights, such as the Child Protection Law (Wadeema).